Electronic health records with decision support systems for sharper diagnoses: bibliometric analysis - Abdelaziz, Toka; Rosa, Elyse Maria (International Journal of Advances in Applied Sciences, 2024)
Clinical decision support systems (CDSS) and electronic health records (EHRs) are computer systems designed to assist decision-makers in making optimal and streamlined judgments on disease diagnosis, treatment, patient care, and health institution management. This study conducted descriptive and bibliometric evaluations of CDSS integrated with EHRs studies published in journals included in the Scopus database from 2007 to 2024. During the initial phase, the publications were distributed based on their publication year, nation, institution, journal, and citation numbers, as part of a descriptive analysis. During the second stage, the articles were subjected to bibliometric analysis, which involved doing common keyword analyses. The research yielded 409 papers about CDSS and EHRs. The United States has been identified as the country with the highest number of studies on this issue. The journal with the highest number of citations observed was Studies in Health Technology and Informatics. Furthermore, the text showcases visual representations of co-citations and cooperation between authors from different institutions and countries. This study aims to present a systematic framework for examining CDSS with EHRs to improve diagnosis and offer a comprehensive viewpoint to researchers and specialists in the field.